2013
DOI: 10.1097/gco.0b013e32836024cb
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on male fertility

Abstract: Aging has an impact on male fertility potential, as well as potential genetic effects for the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Interestingly, our data suggest that only advanced paternal age is associated with cleft palate, whereas no significant relationship appeared between advanced maternal age at conception and the risk of cleft palate. It is now well established that male reproductive function declines with age [29,30]. Furthermore, a landmark study [31] published in 2012 identified that the diversity in the mutation rate of single nucleotide polymorphism (SNP) in the offspring increased by two mutations per year based on paternal age at conception of children.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data suggest that only advanced paternal age is associated with cleft palate, whereas no significant relationship appeared between advanced maternal age at conception and the risk of cleft palate. It is now well established that male reproductive function declines with age [29,30]. Furthermore, a landmark study [31] published in 2012 identified that the diversity in the mutation rate of single nucleotide polymorphism (SNP) in the offspring increased by two mutations per year based on paternal age at conception of children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies observed the following generalities: a) Increased age is associated with a higher rate of de novo mutations and other genomic abnormalities in male germ cells (Crosnoe and Kim, 2013; Singh et al, 2003); b) Such abnormalities are more common in schizophrenia than in normal controls (Walsh et al, 2008); and, c) Older paternal age is associated with greater risk of schizophrenia (Malaspina, 2001). A model that explains how a) and b) could imply c) is that de novo mutations and other genomic abnormalities are more frequently among the contributing factors leading to schizophrenia when the proband has an older father versus a younger one (Kong et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…However, studies analyzing male age have demonstrated declines in structural and functional parameters and established the age of 40 as a cutoff or turning point ( Guérin et al ., 2005 ; Evenson & Wixon, 2006 ; Belloc et al ., 2008 ). Additionally, studies have indicated that advanced paternal age increases the risk of miscarriage ( Slama et al ., 2005 ; Kleinhaus et al , 2006 ) and the potential of certain diseases occurring in the offspring, such as genetic abnormalities, pediatric cancer, and several neuropsychiatric disorders ( Hemminki & Kyyrönen, 1999 ; Wyrobek et al ., 2006 ; O’Roak et al ., 2012 ; Crosnoe & Kim, 2013 ; Paul & Robaire, 2013 ). Advanced male age has also been correlated with infant mortality ( Urhoj et al ., 2014 ).…”
Section: Introductionmentioning
confidence: 99%